The Use of Kledo Application in Job Order Costing Calculations at the Mahadi Konveksi - Sulik Sofinda; Sugeng Santoso (Journal of Economics, Management and Accounting (JEMA), 2025)
MSMEs are a vital pillar of the Indonesian economy, yet many still face challenges in financial management. One common challenge is manual record-keeping, which is prone to errors and takes a long time. This reserach aims to analyze the implementation of the cloud-based accounting application Kledo at the Mahadi Konveksi MSME in Blitar, specifically in calculating job order costing. The research method used was descriptive qualitative with a case reserach approach. Data were obtained through observation, interviews, and documentation of financial reports for the January–June 2023 period. The results show that implementing Kledo provides several tangible benefits for Mahadi Konveksi. The transaction recording process is faster and more organized, while the calculation of job order cost is more accurate than manual methods. Furthermore, the resulting financial reports are more transparent and easier to understand, allowing them to be used directly as a basis for business decision-making. However, challenges were still encountered in the initial stages, such as employee adaptation to the new system and dependence on the internet network. These challenges are temporary and can be overcome through training and infrastructure improvements. Overall, this reserach confirms that the Kledo application can be a practical solution to improve the efficiency, accuracy, and professionalism of MSME financial management.